Phospholipase A(2) modulates respiratory burst developed by neutrophils in patients with rheumatoid arthritis - Bostan, Marinela (J Cell Mol Med, 2007)
Activated by bacterial peptides, phorbol esters, calcium ionophores and other agonists, neutrophils (PMNs) release the proinflammatory mediator, arachidonic acid (AA) via the intervention of phospholipase A(2) (PLA(2)). AA may play an essential role in activation of NADPH‐oxidase, which is involved in the generation of superoxide anion by neutrophils. The present study is focused on the involvement of PLA(2) in the respiratory burst developed by PMNs isolated from patients with rheumatoid arthritis (RA). PLA(2) exists in very high levels in diseases such as rheumatoid arthritis and may cause acute inflammatory and proliferative changes in synovial structures. The respiratory burst was evaluated as superoxide anion release, using an amplified chemiluminiscence method. The assays were performed using PMNs untreated or treated with different doses of stimulatory reagents (phorbol 12‐myristate‐13‐acetate (PMA), calcium ionophore (A23187)). Our data suggested that PMA stimulated the production of superoxid anion in a dose‐response manner, as compared with A23187, which did not induce a significant release of superoxide anion in PMNs‐RA. The exogenous addition of AA significantly amplified the superoxide anion release by PMNs‐RA stimulated with PMA and to a lesser extent, by PMNs stimulated with A23187. AA has also reversed the inhibitory effect of arachidonyl‐trifluorometylketone and E‐6‐(bromomethylene)tetrahydro‐3‐(1‐naph‐thalenyl)2H‐pyran‐2‐one (BEL) on the superoxide anion release by PMNs‐RA. In conclusion, the differential responses to these two agents suggested that different isoforms of PLA(2) were activated by A23187 or PMA, and support the idea that activation of these different PLA(2) served distinct functions of PMNs. Therefore, the inhibition of PLA(2) enzymes might be of great importance in the immunotherapy of rheumatoid arthritis.